Pengelolaan Piutang Dagang Perusahaan: Studi Kasus Pada PT Elegant Indonesia - Javany, Vega; Rachman, Rachmawaty; Andrianto, Toni (Jurnal Aplikasi Bisnis Kesatuan, 2024)
Accounts receivable is one of the important assets for a company. Effective management of accounts receivable can contribute to the company's financial success and reduce the risk of losses due to delinquent payments. The management of accounts receivable involves a series of activities that include determining credit policies, monitoring customers, effective collection, handling bad debts, and reporting, as well as the use of appropriate information systems. Companies need to have a clear credit policy to control customer credit risk. In addition, regular customer monitoring can help identify customers who have poor payment potential or are experiencing financial difficulties. PT Elegant Indonesia located at Jalan Lintang raya Kav F7 Sentul Industrial Estate, Bogor is a private company engaged in the automotive sector that sells products such as car seat covers, sofa covers, motorcycle seat covers, velvet carpets, and other car accessories. PT Elegant Indonesia's operational activities are carried out on credit. So that it will cause receivables and management of these receivables. Therefore controlling it is needed (SOP) so that it has a good impact on the company. The purpose of this study is to discuss the understanding, of the importance of managing accounts receivable.   Keywords: Trade Receivables